2019
DOI: 10.1177/2055207619842986
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mobile application interventions for the treatment of post-traumatic stress disorder: A systematic review

Abstract: Background Many adults with post-traumatic stress disorder (PTSD) are unable to access healthcare services for treatment due to logistical, social, and attitudinal barriers. Interventions delivered via mobile applications (apps) may help overcome these barriers. Objective The aim of this study is to systematically evaluate the most recent evidence from trials investigating the efficacy of mobile apps for treating PTSD. Methods PubMed, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…The median of the user ratings (maximum five stars) was 4.3 (M = 4.2, SD = 0.7) (last updated on 15 May 2019). One app ('PTSD coach') was evaluated in several studies, including an RCT (Kuhn et al, 2017(Kuhn et al, , 2018Miner et al, 2016;Possemato et al, 2016;Wickersham, Petrides, Williamson, & Leightley, 2019). The 'CBT-I coach' app was evaluated in a feasibility pilot RCT (Koffel et al, 2018).…”
Section: General Characteristicsmentioning
confidence: 99%
“…The median of the user ratings (maximum five stars) was 4.3 (M = 4.2, SD = 0.7) (last updated on 15 May 2019). One app ('PTSD coach') was evaluated in several studies, including an RCT (Kuhn et al, 2017(Kuhn et al, , 2018Miner et al, 2016;Possemato et al, 2016;Wickersham, Petrides, Williamson, & Leightley, 2019). The 'CBT-I coach' app was evaluated in a feasibility pilot RCT (Koffel et al, 2018).…”
Section: General Characteristicsmentioning
confidence: 99%
“…It is discernable that this field of research is underpowered and conclusions about the benefits of smartphone-based applications cannot be drawn on single trials alone. A recent study (Wickersham et al, 2019) reviewed the efficacy of mobile interventions, both self-managed and with clinician support, for the treatment of PTSD symptoms in randomized controlled trials (RCTs) and found inconclusive yet promising results, with a decrease of symptoms in app-based treatments, but not compared to control groups. To evaluate the efficacy of self-managed apps alone, further granulation and metaanalysis of individual studies is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, eight systematic reviews and meta-analyses investigating DBIs for non-complex PTSD have been published since 2016 (Kuester et al, 2016;Lewis et al, 2019;Sijbrandij et al, 2016;Simblett et al, 2017;Simon et al, 2019;Turgoose et al, 2018;Wickersham et al, 2019;Young & Campbell, 2018), with a ninth currently under development (Steubl et al, 2019). Across these reviews, the literature supports the effectiveness of internet-based CBT (i-CBT) for reducing symptoms of PTSD, showing superiority to TAU/waitlist conditions, and equal effectiveness to in-person CBT (Knaevelsrud & Maercker, 2007;Kuester et al, 2016;Lewis et al, 2018;Lewis et al, 2019;Sijbrandij et al, 2016;Simblett et al, 2017;Young & Campbell, 2018).…”
Section: Digital-based Interventions For Traumamentioning
confidence: 99%